1998
DOI: 10.1046/j.1432-1327.1998.2550766.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin‐induced reversal of astrocyte stellation is mediated by activation of protein kinase C β‐1

Abstract: Exogenous or endogenous injuries of the central nervous system trigger astrogliosis characterized by proliferation of astrocytes and changes in their morphology from stellate to flat polygonal. Astrocytes in culture are very sensitive to thrombin, a serine protease, which through its proteolytically activated receptor (PAR-1) induces proliferation and morphological changes comparable to astrogliosis. Evaluation of the thrombin signal-transduction pathway in the reversal of astrocyte stellation might help to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 67 publications
3
27
0
Order By: Relevance
“…This may explain the discrepancy with the results of Davenport (Davenport et al, 2000) who did not observe such an effect since these authors used only low thrombin concentrations. It is well known that thrombin efficient concentrations depend on the cell-type studied and range from picomolar concentration for reversal of astrocyte stellation (Beecher et al, 1994;Pindon et al, 1998) to nanomolar concentration for tumor cell apoptosis (Zain et al, 2000) and micromolar concentrations for neuronal apoptosis (Donovan et al, 1997). Under our conditions, thrombin did not induce myotube apoptosis as shown by TUNEL analysis and annexin V binding (data not shown).…”
Section: Discussionsupporting
confidence: 54%
“…This may explain the discrepancy with the results of Davenport (Davenport et al, 2000) who did not observe such an effect since these authors used only low thrombin concentrations. It is well known that thrombin efficient concentrations depend on the cell-type studied and range from picomolar concentration for reversal of astrocyte stellation (Beecher et al, 1994;Pindon et al, 1998) to nanomolar concentration for tumor cell apoptosis (Zain et al, 2000) and micromolar concentrations for neuronal apoptosis (Donovan et al, 1997). Under our conditions, thrombin did not induce myotube apoptosis as shown by TUNEL analysis and annexin V binding (data not shown).…”
Section: Discussionsupporting
confidence: 54%
“…We demonstrate that PAR-1 expression in astrocytoma cells is up-regulated by thrombin, but the signaling pathways remain to be elucidated. PAR-1 and thrombin protein expression was predominantly detected on reactive astrocytes in HIVE brains, suggesting a potential important autocrine loop leading to immune activation, calcium signaling (77), and astrogliosis (14). PAR-1 immunoreactivity was also observed on neurons, endothelial cells, and infiltrating monocytic cells, although to a much lesser extent.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, thrombin seems to induce microglial activation by induction of DNA synthesis as well as production of nitric oxide and tumor necrosis factor-␣ (Ryu et al, 2000;Suo et al, 2002). Many groups have also demonstrated that PAR-1 activation stimulates astrocytes to transform from their normally stellate shape into a polygonal morphology (Beecher et al, 1994;Grabham and Cunningham, 1995;Suidan et al, 1997;Pindon et al, 1998). In addition, thrombin also induces endothelin-1 and nerve growth factor secretion from astrocytes (Ehrenreich et al, 1993;Neveu et al, 1993;Debeir et al, 1996).…”
Section: Discussionmentioning
confidence: 99%